Design of Optically Transparent Antenna with Directional Radiation Patterns - Yuan Yao; Wanzhong Chen; Xiaodong Chen; Junsheng Yu (International Journal of Antennas and Propagation)
An optically transparent antenna with directional radiation pattern is proposed in this paper. This antenna consists of a radiation patch above the transparent glass substrate and a frequency selective surface acting as the ground of microstrip antenna on the back of the glass. The frequency selective surface (FSS) performs well as ground in the working frequency range to achieve directional radiation pattern. A SMA connector is used to feed the antenna. The antenna can operate at the on-board dedicated short-range communication band from 5.725 GHz to 5.85 GHz. Simulations and measurements are carried out to study the antenna performances in terms of impedance matching, gain, and radiation patterns. Both of the simulation and measurement results are shown to illustrate the good performance of the proposed antenna. It is very suitable for car network communication scene.